Management of tamarind bruchid, Caryedon serratus with seed protectants and their effect on stored groundnut seed - Patta, Sujatha; Keshavulu, K; Radhika, K (Indian Journal of Plant Protection, 2020)
The effect of seven chemicals and two botanical seed protectants was studied against tamarind bruchid, Caryedon serratus under ambient storage conditions on groundnut pods at the Department of Seed Science and Technology, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad. Among seed protectants, imidacloprid exhibited maximum level of effectivity, persistency and residual toxicity against C. serratus followed by chlorpyriphos, bifenthrin, deltamethrin and malathion. Comparatively, thiamethoxam and diflubenzuron did not show promising persistency against this pest at later stages of treatment, eventhough they performed well in the initial stages of the treatment. However, botanicals like Lantana camara and custard apple leaf powders reported fast degradation in their toxicity levels even from 15 days after treatment and failed to show required amount of persistence and residual toxicity. Six months after treatment, irrespective of the seed protectants used all the seed showed a gradual reduction in all seed quality parameters. Irrespective of seed protectants used, per cent germination was recorded above seed certification standards. High germination of 88% was recorded with deltamethrin, imidacloprid, diflubenzuron, lantana and custard apple leaf powder and untreated control, whereas low germination (%) was recorded in the seeds treated with thiamethoxam (75%). Seedling vigour index (SVI) was marginally lesser in chemical treatments when compared with botanicals and untreated control. Except thiamethoxam, the seed treated with all other seed protectants recorded no significant reduction in the seed germination and seedling vigour index.